Adsorpsi Zat Warna Rhodamin B Menggunakan Karbon Aktif Dari Tandan Kosong Kelapa Sawit (Elaeis Guneensis Jacq) - Utami Utami; Shinta Elystia; Yelmida Aziz (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Textile industry is one of the most dominant developed industries in Indonesia. Waste textile industries were dominated by dyes pollution from the production process. One way to pigment used in textile industry is pigment Rhodamin B. Methodt reduce dyes waste pollution is through adsorption. The adsorbent that used was activated carbon from waste palm empty fruit buncheswhich are activation physics in temperature 300oC and chemical activation is done by using H3PO4 activator. This research aims to study the activated carbon capabilities in adsorption Rhodamin B in the variation of the mass of adsorbent 1, 3 and 5 grams, sieve size 0,595-250 mm, 0,250-125 mm and 0,105 mm and a contact time of 15, 30, 45 and 60 minutes.The results showed that the optimum occurs at mass 5 grams, sieve size 0,105 mm and a contact time of 45 minutes with an efficiency of 99,50%. While the lowest efficiency is 27% to mass 5 grams, particle size 0,595-0,250 mm and a contact time 15 minutes.Keywords: Adsorption, Activated carbon palm empty fruit bunches, Adsorbent mass, Sieve size , Contact time, Rhodamin B